1999
DOI: 10.1080/096382899297585
|View full text |Cite
|
Sign up to set email alerts
|

Promoting group empowerment and self-reliance through participatory research: a case study of people with physical disability

Abstract: This case study demonstrates how group participation, promoted by a critically informed therapeutic and research praxis, can unlock the inherent potential for self-reliance and empowerment of socially marginalized collectives. It offers important insights with regard to group process, participatory research and the role of the health professional in creating opportunities for empowerment and self-reliance of people with disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…The 11 selected studies looked at DPOs operating in: Nepal (Dhungana and Kusakabe, 2010); Bangladesh (Miles et al, 2012;Polu et al, 2015); the South Asian coastline (Hemingway and Priestley, 2006); Africa (Stewart and Bhagwanjee, 1999;Kleintjes et al, 2013); India (Kumaran, 2011;Cobley, 2013;Deepak et al, 2013); Bolivia (Griffiths et al, 2009); Brazil and India (Deepak et al, 2013); and Malaysia (Armstrong, 1993). Thus, 9 studies involved DPOs operating in low or lower-middle income countries (Hemingway and Priestley, 2006;Griffiths et al, 2009;Dhungana and Kusakabe, 2010;Kumaran, 2011;Miles et al, 2012;Cobley, 2013;Deepak et al, 2013;Kleintjes et al, 2013;Polu et al, 2015) and four included DPOs operating in upper-middle income settings (Armstrong, 1993;Stewart and Bhagwanjee, 1999;Deepak et al, 2013;Kleintjes et al, 2013). This review revealed that, as yet, there is no published literature above level three evidence on the Oxford Centre for Evidence-Based Medicine (OCEBM) hierarchy of evidence (2011) concerning the function of DPOs in LMICs (i.e., the highest level of evidence identified in this review was a cohort study design).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 11 selected studies looked at DPOs operating in: Nepal (Dhungana and Kusakabe, 2010); Bangladesh (Miles et al, 2012;Polu et al, 2015); the South Asian coastline (Hemingway and Priestley, 2006); Africa (Stewart and Bhagwanjee, 1999;Kleintjes et al, 2013); India (Kumaran, 2011;Cobley, 2013;Deepak et al, 2013); Bolivia (Griffiths et al, 2009); Brazil and India (Deepak et al, 2013); and Malaysia (Armstrong, 1993). Thus, 9 studies involved DPOs operating in low or lower-middle income countries (Hemingway and Priestley, 2006;Griffiths et al, 2009;Dhungana and Kusakabe, 2010;Kumaran, 2011;Miles et al, 2012;Cobley, 2013;Deepak et al, 2013;Kleintjes et al, 2013;Polu et al, 2015) and four included DPOs operating in upper-middle income settings (Armstrong, 1993;Stewart and Bhagwanjee, 1999;Deepak et al, 2013;Kleintjes et al, 2013). This review revealed that, as yet, there is no published literature above level three evidence on the Oxford Centre for Evidence-Based Medicine (OCEBM) hierarchy of evidence (2011) concerning the function of DPOs in LMICs (i.e., the highest level of evidence identified in this review was a cohort study design).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review were observational and, in general, did not investigate outcome data before and after the formation of DPOs, with the majority of papers presenting single point-in-time or short-term data. The majority were descriptive case studies or case series (Armstrong, 1993;Stewart and Bhagwanjee, 1999;Griffiths et al, 2009;Dhungana and Kusakabe, 2010;Miles et al, 2012;Cobley, 2013;Deepak et al, 2013;Polu et al, 2015). Three studies had features of cross-sectional design; however, the methodology was not clear (Hemingway and Priestley, 2006;Kumaran, 2011;Kleintjes et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free transportation is widely available in Taiwan [44], however it is used less frequently by people with disabilities. In addition, patient-family support groups have been developed for patients with cancer or disabilities, and have been shown to be helpful in improving adjustment and self-reliance [45,46]. To boost the utilization rate in this subgroup, healthcare authorities may need to address these points by providing more resources and initiative services.…”
Section: Discussionmentioning
confidence: 99%